2015
DOI: 10.4103/0973-1296.157679
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and apoptotic effects of Ebenus boissieri Barbey on human lung cancer cell line A549

Abstract: Background:Fabaceae family members are known to possess preventive and therapeutic potentials against various types of cancers.Objective:The aim of this study was to investigate the cytotoxic and apoptotic effects of hydroalcoholic extracts from the aerial parts and roots of an endemic Ebenus species; Ebenus boissieri Barbey in human lung cancer cell line.Materials and Methods:After treatment with hydroalcoholic extracts cytotoxic activities of both extracts were measured by 3-(4,5-dimethylthiazolyl-2)-2,5-dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The World Health Organization estimates that 4 billion people (i.e., 80% of the World's population) use herbal medicines in some aspects of primary healthcare, and there is a growing tendency to “Go Natural.”;[ 1 2 ] It is well established that plants have always been a useful source, for the occurrence of anticancer compounds. [ 3 4 5 ] Approximately 60% of the currently used anticancer chemotherapeutic drugs (vinblastin, vincristine) are derived from plant resource. [ 6 7 ] Although most of the plants used in the traditional medicine have been identified and their applications are well-documented, the anticancer efficacy of many plants is yet to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that 4 billion people (i.e., 80% of the World's population) use herbal medicines in some aspects of primary healthcare, and there is a growing tendency to “Go Natural.”;[ 1 2 ] It is well established that plants have always been a useful source, for the occurrence of anticancer compounds. [ 3 4 5 ] Approximately 60% of the currently used anticancer chemotherapeutic drugs (vinblastin, vincristine) are derived from plant resource. [ 6 7 ] Although most of the plants used in the traditional medicine have been identified and their applications are well-documented, the anticancer efficacy of many plants is yet to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…The dose range (0.01-1000 μg/mL) was determined for both plant extracts and Doxorubicin-HCl in our previous study. [ 19 ] As shown in Figure 1A and 1B , root extract had more inhibitory activity on proliferation of 293T than HeLa cells. In HeLa cells, the IC 50 of aerial and root extract were approximately 92.35 ± 0.39, 49.82 ± 0.27, 28.03 ± 0.12 μg/mL and 250 ± 5.83, 100.16 ± 4.28, 41.04 ± 1.09 for 24, 48, and 72 h, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…In support of our study on medicinal plants against cancer, a recent research has reported that Fabaceae family members possess preventive and therapeutic potentials against various types of cancers. They demonstrated that the hydroalcoholic extracts of Ebenus boissieri barbey has anti-apoptotic and anti-carcinogenic activity against lung cancer cell line A549 (Aydemir et al, 2015).…”
Section: Discussionmentioning
confidence: 99%